This day in June - Pitman, Gayle E.; Litten, Kristyna (Washington, DC Magination Press, 2014)
"A picture book illustrating a Pride parade. The endmatter serves as a primer on LGBT history and culture and explains the references made in the story"-- Provided by publisher.
"American Psychological Association."
UCWS-2014-G-2025 donated by Dr. Anna Tuazon
Keywords: Stories in rhyme; Gay pride parades -- Fiction; Parades -- Fiction